Demyelination in experimental intraventricular neurocysticercosis - MOURA, Vania Beatriz Lopes; MILHOMEM, Analia Cirqueira; LIMA, Sarah Buzaim; MATOS-SILVA, Hidelberto; SUGITA, Denis Masashi; VINAUD, Mariana Clare; LINO-JÚNIOR, Ruy de Souza (Arquivos de Neuro-Psiquiatria, 2020)
Neurocysticercosis (NCC) is classified as a neglected tropical disease, which affects mainly Latin America and Africa in spite of some reports in North America and Europe. NCC represents the cause of up to 30% of the reported cases of epilepsy in endemic countries. The NCC injuries present direct relation to the development stage, location, and number of parasites as well as to the host immune response. This study aimed the characterization of the inflammatory response and tissue injuries by means of the analyses of the periventricular and parenchymatous demyelination through the experimental intraventricular NCC infection. Therefore, BALB/c mice were submitted to experimental NCC inoculation with Taenia crassiceps cysticerci. Their brains were removed at 7, 30, 60, and 90 days after the inoculation (DAI), and analyzed after staining with hematoxylin and eosin (HE), Luxol Fast Blue, and Nissl. It was possible to observe ventriculomegaly, inflammatory infiltration composed by polymorphonuclear and mononuclear cells, and foamy macrophages. The presence of inflammatory cells was associated with neurodegeneration detected by the areas with demyelination observed initially in the periventricular area and lately in the parenchyma. In conclusion, the presence of cysticerci and the consequent inflammation were able to promote initial periventricular demyelination followed by parenchymatous demyelination as the infection progressed.
Keywords: neurocysticercosis; periventricular demyelination; parenchymal demyelination; Taenia crassiceps